2017
DOI: 10.1038/srep42173
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-A5 organized in 2D-network at the plasmalemma eases human trophoblast fusion

Abstract: Only a limited number of human cells can fuse to form a multinucleated syncytium. Cell fusion occurs as part of the differentiation of some cell types, including myotubes in muscle and osteoclasts in remodeling bone. In the differentiation of the human placenta, mononuclear cytotrophoblasts aggregate and fuse to form endocrinologically active, non-proliferative, multinucleated syncytia. These syncytia allow the exchange of nutrients and gases between the maternal and fetal circulation. Alteration of syncytial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 54 publications
0
19
0
2
Order By: Relevance
“…We found that coculturing of cancer and muscle cells boosts the expression levels of Syn1 and AnxA5, proteins associated with several fusion processes (4,6,7,30). The coculturing with hMYOs increased levels of Syn1 and AnxA5 gene expression ( Fig.…”
Section: Muscle Cell-promoted Fusion Of Cancer Cells Depends On Syn1 mentioning
confidence: 70%
See 2 more Smart Citations
“…We found that coculturing of cancer and muscle cells boosts the expression levels of Syn1 and AnxA5, proteins associated with several fusion processes (4,6,7,30). The coculturing with hMYOs increased levels of Syn1 and AnxA5 gene expression ( Fig.…”
Section: Muscle Cell-promoted Fusion Of Cancer Cells Depends On Syn1 mentioning
confidence: 70%
“…Numbers of viable PC3 cells after a 24-hour application of the drug were normalized to the numbers in corresponding controls not treated with the drug. PC3 cells (1); PC3 cells grown in the presence of either Syn1 peptide (3) or scrambled Syn1 peptide (2); PC3 cells cocultured in a direct contact with hMYOs (4), PC3 cells cocultured with hMYOs in the presence of either Syn1 peptide (6) or scrambled Syn1 peptide (5). All results are shown as means AE SEM (n !…”
Section: Formation Of Multinucleated Prostate Cancer Cells Depends Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The small GTPase Ran, which plays an important role in nucleocytoplasmic shuttling, 28,29 showed a high L/H ratio in all three data sets. By contrast, the cytoplasmic protein ANXA5 [30][31][32] had a high L/H ratio only in the BioID2 and BioID2PAD2 comparison ( Figure 3C left panel). The L/H ratio of FXR1, which localizes in the nucleus, [33][34][35] increased in the presence of calcium, consistent with our finding that calcium triggers the entry of PAD2 into the nucleus.…”
Section: Combined Bioid2 and Silac Approaches Identify Pad2 Interactimentioning
confidence: 94%
“…Homotypic fusion typically represents the final steps of cell maturation; and therefore, cells must often reach a certain differentiation state to achieve fusion. For example, it was recently shown that trophoblast fusion requires the assembly of a matrix of annexin A5 at the plasma membrane, a process that only occurs in later stages of maturation, to facilitate cell aggregation as a prerequisite for fusion (12). The resultant syncytiotrophoblast is a tremendous and essential benefit for the placenta because it effectively bars immune cells from the mother from invading the fetus and secretes large quantities of hormones needed to support pregnancy.…”
mentioning
confidence: 99%